Relationship between Life Expectancy, Foreign Direct Investment and Trade Openness: Evidence from Turkey - Bese, Emrah; Kalaycı, Salih (Economic Laboratory Transition Research Podgorica-Elit, 2021)
This is the first study in the single country studies that analyze the relationship between life expectancy, foreign direct investment and trade openness for Turkey for the period 1974 to 2017. The long run relationship between variables is analyzed by ARDL (Autoregressive Distributed Lag) model. Short run and long run causal relationships between variables are analyzed by VECM (Vector Error Correction) model. Nonlinear ARDL model is also used to analyze the non-linear relationships between the variables. Hypotheses, that are examined in this study, are impact of FINV net inflow and TOPEN on LEXP, unidirectional causality running from FINV net inflow and TOPEN to LEXP, asymmetric relationship between LEXP, FINV net inflow and TOPEN and asymmetric relationship between FINV net inflow and TOPEN in Turkey. According to the results in this study, long run relationship is found between the variables, and foreign direct investment affects significantly and positively life expectancy in the long run. No causal relationship from foreign direct investment and trade openness to life expectancy is found in the long run and in the short run. Trade openness does not significantly affect life expectancy in the long run. Nonlinear relationship between the variables is also not confirmed. Asymmetric relationship between trade openness and foreign direct investment is confirmed. While decrease in trade does not have a significant impact on foreign direct investment, increase in trade has a significant positive impact on foreign direct investment.
Keywords: Life expectancy; ARDL model; foreign direct investment; VECM; Turkey; trade openness